Pengaruh Kompetensi Profesional Guru dan Penghayatan Etika Profesi Guru terhadap Kinerja Guru - Sandi Saparudin; Rian Hidayat; Rinita Dewi; Lidya Mustikasari; Sri Wahyuni (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2022)
This research aims to determine the effect of teacher professional competence and appreciation of teacher professional ethics on teacher performance. This research is quantitative research in elementary schools in the district of Cilawu, Garut Regency. The data collection technique used in this research is a survey technique. The results of this research are 1) The professional competence of teachers all show very good criteria because all respondents' answers regarding these aspects are in good criteria, 2) The appreciation of teacher professional ethics results show very good criteria because the average respondent's answers regarding these aspects are on very good criteria, 3) Teacher performance shows good criteria because the average respondents' answers regarding these aspects are in good criteria.